Jüdinnen in der frühen italienischen Frauenbewegung (1861-1945) - Nattermann, Ruth (2020)
The study explores the experiences of Italian Jewish women in the context of Italian politics and society since the inception of the liberal unitary state, during the First World War, and under the fascist dictatorship through 1945. Using sources accessible for the first time, the study casts new light on 19th- and 20th-century Italian and Italian-Jewish history and its European and international connections.